UJI AKTIVITAS ANTIBAKTERI FACE MIST EKSTRAK ETANOL DAUN ANDONG MERAH (Cordyline fruticosa (L) A. Chev.) TERHADAP Propionibacterium acnes - Eko Sri Wahyuningsih; Melisa Puspitasari; Neni Sri Gunarti; Maulana Yusuf Alkandahri (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2023)
This research is motivated by the problem of skin infection in the form of acne, one of the causes of which is the bacterium Propionibacterium acnes. Red andong leaves contain several secondary metabolites that have the potential as antibacterials such as flavonoids, tannin, saponins,and polyphenolic. The purpose of this study was to make a face mist preparation formula from red andong leaf extract which has the potential as an antibacterial for Propionibacterium acnes. The extraction method used was maceration with 70% ethanol solvent. Testing the inhibition of antibacterial activity was carried out using the well-diffusion method. Determination of the concentration of the extract needed for face mist preparation is taken from the results of the MIC test. Face mist preparations were made with 3 concentrations, namely formulas F3.12, F6.25, and F9.37. The face mist base was used as a negative control and the face mist base added with clindamycin powder was used as a positive control. Testing the face mist of red andong leaves extract included organoleptic, homogeneity, specific gravity, pH, spray spreadability, dry time, and hedonic tests. The results showed that the face mist of the ethanol extract of red andong leaves extract met the requirements for a good face mist preparation and had an inhibitory effect on the growth of Propionibacterium acnes bacteria in all formulas. Face mist Formulation 3.12% has an inhibition of 8.19 ± 0.22 mm, Formulation 6.25% has an inhibition of 10.59 ± 0.13 mm, and Formulation 9.37% has an inhibition of 11.75 ± 0.17 mm. From this study, it can be concluded that face mist containing 9.37% (F9.37) of red andong leaf extract was the most effective formulation against Propionibacterium acnes bacteria with the highest inhibition zone diameter of 11.75 ± 0.17 mm.